Maximum Power Point Tracking Algorithms Under Partial Shading Condition (International Journal of Innovative Research in Computer Science & Technology, 2022)
High and rising fuel consumption has  occurred in past times. resulted in enormous growth in  renewable energy generation and consumption. As  economies Photovoltaic (PV) solar is becoming more  popular as the world's interest in cleaner energy grows. is  becoming a more viable option. PV energy harvesting and  managing has numerous advantages, but it also has certain  disadvantages, such as low energy conversion efficiency  due to optical and electrical losses. Because of the random  component associated with its genesis, the partial shading  problem, the first of these losses is typically the most  hardest to deal with. As a result, shading countermeasures  exist as an important component of power converting unit,  so as to reduce negative influence over power efficiency  extraction. Despite the fact that each of these processes has  its own set of shortcomings, a large range of different  techniques have been devised as well as evaluated in literature to far. We proposes a MATLAB simulation to investigate the efficiency of set of numerous high power  point tracking approaches over a large range of shading  speeds, where PV array layout is created in three different  settings under various partial shading conditions.
Keywords: Photovoltaic (PV); Maximum Power Point Tracking (Mppt); Deterministic Algorithms; Stochastic Algorithms